Influenza epidemiology and immunization during pregnancy: final report of a World Health Organization working group - Fell, DB; Azziz-Baumgartner, E; Baker, MG; Batra, M; Beauté, J; Beutels, P; Bhat, N; Bhutta, ZA; Cohen, C; De Mucio, B; Gessner, BD; Gravett, MG; et al. (Elsevier, 2017)
From 2014 to 2017, the World Health Organization convened a working group to evaluate influenza disease burden and vaccine efficacy to inform estimates of maternal influenza immunization program impact. The group evaluated existing systematic reviews and relevant primary studies, and conducted four new systematic reviews. There was strong evidence that maternal influenza immunization prevented influenza illness in pregnant women and their infants, although data on severe illness prevention were lacking. The limited number of studies reporting influenza incidence in pregnant women and infants under six months had highly variable estimates and underrepresented low- and middle-income countries. The evidence that maternal influenza immunization reduces the risk of adverse birth outcomes was conflicting, and many observational studies were subject to substantial bias. The lack of scientific clarity regarding disease burden or magnitude of vaccine efficacy against severe illness poses challenges for robust estimation of the potential impact of maternal influenza immunization programs.